Theoretical and experimental investigation of liquid droplets flashing for low cost seawater desalination - Alrowais, Raid (KAUST Research Repository, 2020)
The high specific energy consumption from all existing seawater desalination methods has heightened the motivation for having more efficient and greener desalination processes to meet the future goals of sustainable seawater desalination. One of the promising thermally-driven desalination methods is the direct-contact spray evaporation and condensation (DCSEC) where the excess enthalpy between feed and equilibrium states of evaporator chambers is exploited with reasonably high flashing efficiency. Further improvements in energy efficacy of DCSEC are boosted by firstly the incorporation of micro/nano-bubbles (M/NB) where micro or nano size subcooled vapor are embedded in the sprayed liquid droplets of evaporator, thereby lowering the temperature brine in evaporator and minimizing the thermal equilibrium effect of brine. The presence of subcooled bubbles increased the available surface area for heat transfer. Secondly, the concept of an evaporator-condenser pair of DCSEC could be extended to a multi-stage arrangement where the latent heat of vapor condensing on the water droplets sprayed within the condenser is recovered. From the experiments, the effect of incorporating the (M/NB) in the DCSEC at optimum feed flow rate yields more than 34% increase in distillate production at feed temperatures greater 47oC and the cooling inlet temperature set at 35oC. The other salient improvement found from the experiments is the increase in performance ratio (PR) up to 3.3 for a 6-stage configuration. This quantum jump in the PR is attributed to the heat recovery effect by as much as 70% of the total heat input. Arising from the DCSEC design, the implicit benefits are the low capital and operational cost, i.e., low CAPEX and OPEX. The former savings is attributed zero physical interfaces such as tube-based heat exchangers or membranes, whilst the latter savings is contributed by significant lesser use of chemicals in the pre-treatment of seawater feed. Lastly, the accompanied benefit is the robustness of the DCSEC processes where it could within stand high salinity of the brine, typically as high as 200,000 ppm.